Progressive Muscle Relaxation Therapy as an Alternative for Managing Stress During the COVID-19 Pandemic in Yapen Islands Regency - Yohanis F. Tipawael; Korinus Suweni; Ardhanari Hendra (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
COVID-19 was first detected in Wuhan, Hubei Province, China. The virus spread rapidly, prompting the World Health Organization (WHO) to classify COVID-19 as a global pandemic. In Indonesia, the virus spread at a fast pace. According to WHO data, there have been 6,535,354 COVID-19 cases globally, with 387,155 deaths. A total of 216 countries, including Indonesia, have been affected by this virus. In Indonesia, there have been 29,521 confirmed cases with 1,770 deaths, while in West Nusa Tenggara (NTB), 798 cases and 22 deaths have been reported. The high number of cases has placed significant stress on the public, both mentally and physically, due to the pressures brought on by the pandemic. This study employed a Quasi-Experimental design with a sample size of 50 respondents, selected using the purposive sampling technique. The study aimed to assess the impact of progressive muscle relaxation techniques on reducing stress levels in the community of Kepulauan Yapen Regency. Based on statistical tests, the average stress score before the intervention was 16.80, which decreased to 11.58 after the intervention with progressive muscle relaxation techniques. There was an average reduction of 5.16 in stress scores, with a p-value of 0.000 <α= 0.05. Conclusion: This study concluded that progressive muscle relaxation therapy has a significant effect on reducing stress levels in the community during the COVID-19 pandemic in Kepulauan Yapen Regency.